The N-Terminal Region of the Ryanodine Receptor Affects Channel Activation - Faltinova, Andrea; Tomaskova, Nataša; Antalik, Marián; Sevcik, Jozef; Zahradnikova, Alexandra (Frontiers in Physiology, 2017)
Mutations in the cardiac ryanodine receptor (RyR2), the ion channel responsible for release of calcium ions from intracellular stores into cytoplasm, are the cause of several inherited cardiac arrhythmias. At the molecular level, disease symptoms can be mimicked by domain peptides from mutation-prone regions of RyR2 that bind to RyR2 and activate it. Here we show that the domain peptide DPcpvtN2, corresponding to the central helix of the N-terminal region of RyR2, activates the RyR2 channel. Structural modelling of interaction between DPcpvtN2 and the N-terminal region of RyR2 in the closed and open conformation provided three plausible structures of the complex. Only one of them could explain the dependence of RyR2 activity on concentration of DPcpvtN2. The structure of the complex was at odds with the previously proposed "domain switch" mechanism of competition between domain peptides and ryanodine receptor domains. Likewise, in structural models of the N-terminal region, the conformational changes induced by DPcpvtN2 binding were different from those induced by mutation of central helix amino acids. The activating effect of DPcpvtN2 binding and of mutations in the central helix could be explained by their similar effect on the transition energy between the closed and open conformation of RyR2.